Perceived stress, alcohol consumption, and Internet use among Korean college students: Does sensation-seeking matter?. (May 2018) - Jang, Soo Mi; Sohn, Sunju; Yu, Mansoo
Abstract: The drinking culture in South Korea is fairly permissive, and the country is one of the world's fastest growing leaders in Internet connectivity. Given very slim knowledge on the mediating role of sensation-seeking on the association between stress, alcohol consumption, and Internet use among Korean college students, a cross-sectional study was conducted using Structural Equation Modeling on 870 college students (Mean age = 21.9 (SD = 2.4), Males: 65.6%). Sensation-seeking positively mediated between perceived stress level and alcohol use, but no effect on Internet use was found. Findings suggest the need to understand the direct effect of stress on drinking as well as linkages between stress, sensation-seeking, and alcohol consumption.